(untitled) (Vietnam Journal of Community Medicine, 2026)
ABSTRACT Objective: To review and evaluate the efficacy and safety of the deep plane facelift technique in the management of facial aging within the community setting. Methods: A narrative literature review was conducted by collecting, selecting, and analyzing both classical and contemporary studies related to facial aging, facial anatomy, surgical indications, deep plane facelift techniques, and clinical outcomes. Only peer-reviewed sources were included, with emphasis on aesthetic improvement, regional facial rejuvenation, and complication rates. Results: Deep plane facelift demonstrated significant improvement in the midface, nasolabial folds, jowls, and jawline, providing more natural and longer-lasting results compared with superficial facelift techniques. However, it is associated with a higher complication rate and requires surgeons with advanced anatomical knowledge and technical expertise. Some cases showed recurrent ptosis when patient selection was suboptimal. Conclusion: Deep plane facelift is an optimal approach for patients with moderate to severe facial aging, offering superior and durable aesthetic outcomes when performed with proper technique and appropriate indications. Nevertheless, safety considerations and careful patient selection remain essential.